Chlamydia trachomatis induces lncRNA MIAT upregulation to regulate mitochondria‐mediated host cell apoptosis and chlamydial development. Issue 1 (3rd December 2021) - Luo, Fangzhen; Wen, Yating; Zhao, Lanhua; Su, Shengmei; Zhao, Yuqi; Lei, Wenbo; Li, Zhongyu
Abstract: Chlamydia trachomatis persistent infection is the leading cause of male prostatitis and female genital tract diseases. Inhibition of host cell apoptosis is the key to maintaining Chlamydia survival in vivo, and long noncoding RNAs (lncRNAs) play important roles in its developmental cycle and pathogenesis. However, it is not clear how lncRNAs regulate persistent Chlamydia infection. Here, using a microarray method, we identified 1718 lncRNAs and 1741 mRNAs differentially expressed in IFN‐γ‐induced persistent C . trachomatis infection. Subsequently, 10 upregulated and 5 downregulated differentially expressed lncRNAs were verified by qRT–PCR to confirm the reliability of the chip data. The GO and KEGG analyses revealed that differentially regulated transcripts were predominantly involved in various signalling pathways related to host immunity and apoptosis response. Targeted silencing of three lncRNAs (MIAT, ZEB1‐AS1 and IRF1) resulted in increased apoptosis rates. Furthermore, interference with lncRNA MIAT caused not only an obvious downregulation of the Bcl‐2/Bax ratio but also a marked release of cytochrome c, resulting in a significantly elevated level of caspase‐3 activation. Meanwhile, MIAT was involved in the regulation of chlamydial development during the persistent infection. Collectively, these observations shed light on the enormous complex lncRNA regulatory networks involved in mitochondria‐mediated host cell apoptosis and the growth and development of C . trachomatis .